2013
DOI: 10.4314/ahs.v13i3.14
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy and its effects on children and families in rural Uganda

Abstract: Background: This report aims to assess the impact of childhood epilepsy in an isolated rural area in Western Uganda, with little access to medical care, via its effect on children and families. Basic information on 440 affected children, clinically examined at 19 rural centres, was collated and data on seizure pattern and duration analysed, together with information on school attendance of older children. Objective: To publicise the consequences of undertreated illness, and to encourage improved management of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 15 publications
2
35
2
Order By: Relevance
“…In addition, female children with epilepsy are at increased risk of developing depression due to the illness which could perhaps affect school attendance negatively. Our finding, however, contradicts the finding of a study that showed higher proportion of school attendance among female than male children (12). The finding of this study shows the need to reach out for female children with epilepsy even more than the male children.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, female children with epilepsy are at increased risk of developing depression due to the illness which could perhaps affect school attendance negatively. Our finding, however, contradicts the finding of a study that showed higher proportion of school attendance among female than male children (12). The finding of this study shows the need to reach out for female children with epilepsy even more than the male children.…”
Section: Discussioncontrasting
confidence: 99%
“…The impact of epilepsy on the family depends on several factors including the severity of the disorder, seizure frequency, adverse effects of treatment, therapeutic response, and induced anxiety in parents and other members of the family [43]. In some studies, depression, anxiety, and sleep disorders were more common among parents of children with epilepsy compared with parents of children without epilepsy [11,44]. Our results were surprising because the QOL was poor in urban areas and among parents whose children had received specialized medical advice.…”
Section: Discussionmentioning
confidence: 98%
“…Epilepsy has been demonstrated to have a big social impact on PWE and their families in Uganda [10], and improving treatment for these patients has the potential of far-reaching consequences.…”
Section: Introductionmentioning
confidence: 99%